The correct statements are A and C.
Statement A is correct because the expression −7(9x − 5) can be simplified by distributing −7 to each term inside the parentheses: −7(9x) − 7(-5) = −63x + 35.
Statement C is correct because the simplified expression is −63x + 35.
Which two statements are correct when simplifying this expression?
−7(9x − 5)
Responses
A First, distribute −7.First, distribute −7.
B First, calculate −7 + (−5).First, calculate −7 + (−5).
C −7(9x −5) = −63x − 35.−7(9x −5) = −63x − 35.
D −7(9x −5) = −63x + 35.−7(9x −5) = −63x + 35.
E −7(9x −5) = 63x − 35.
1 answer